Electrochemical Characterization of Cu-Catalysed Si Nanowires as an Anode for Lithium-Ion Cells. (22nd July 2020) - Prosini, P. P.; Rondino, F.; Moreno, M.; Cento, C.; Ottaviani, M.; Rufoloni, A.; Pilloni, L.; Orsetti, V.; Santoni, A.
Abstract : Silicon (Si) nanowires (NWs) grown on stainless-steel substrates by Cu-catalysed Chemical Vapour Deposition (CVD) have been prepared to be used as anodes in lithium-ion batteries. The use of NWs can overcome the problems related to the Si volume changes occurring during lithium alloying by reducing stress relaxation and preventing material fragmentation. Moreover, since the SiNWs are grown directly on the substrate, which also acts as a current collector, an excellent electrical contact is generated between the two materials without the necessity to use additional binders or conducting additives. The electrochemical performance of the SiNWs was tested in cells using lithium metal as the anode. A large irreversible capacity was observed during the first cycle and, to a lesser extent, during the second cycle. All the subsequent cycles showed good reversibility even if the coulombic efficiency did not exceed 95%, suggesting the formation of an unstable SEI film and a continuous decomposition of the electrolyte on the silicon surface. The absence of a stable SEI film was assumed responsible for a linear capacity fade observed upon cycling. On the other hand, the electrochemical characterization performed at different values of the charging current showed that SiNWs possess an exceptionally high rate capability.